Patient stratification for drug treatment in oncology and other diseases - Harris, Tim (Henry Stewart Talks, 2012)
Personalised medicine in Oncology, Patient stratification using molecular markers, Next generation genome sequencing and data handling, Drivers of patient stratification including payors, Molecular profiling in lung and breast cancer, Relevance of these approaches for ALS, MS and other neurological diseases